Structural transformations in boron clusters induced by metal doping. (14th January 2022) - Barroso, Jorge; Pan, Sudip; Merino, Gabriel
Abstract : Would it be possible to eventually derive a simple methodology to predict the structure adopted by boron clusters based on its structural transformation induced by the doping with one or two metal atoms? Abstract : In the last decades, experimental techniques in conjunction with theoretical analyses have revealed the surprising structural diversity of boron clusters. Although the 2D to 3D transition thresholds are well-established, there is no certainty about the factors that determine the geometry adopted by these systems. The structural transformation induced by doping usually yields a minimum energy structure with a boron skeleton entirely different from that of the bare cluster. This review summarizes those clusters no larger than 40 boron atoms where one or two dopants show a radical transformation of the structure. Although the structures of these systems are not easy to predict, they often adopt familiar shapes such as umbrella-like, wheel, tubular, and cages in various cases.